Production of biodiesel by using CaO nano-catalyst synthesis from mango leaves extraction - Mahmood, Sarah Shakir; Al-Yaqoobi, Atheer Mohammed (Center of Biomass & Renewable Energy (CBIORE), 2024)
Development and population expansion have the lion's share of driving up the fuel cost. Biodiesel has considerable attention as a renewable, ecologically friendly and alternative fuel source. In this study, CaO nanocatalyst is produced from mango leaves as a catalysis for the transesterification of waste cooking oil (WCO) to biodiesel. The mango tree is a perennial plant, and its fruit holds significant economic worth due to its abundance of vitamins and minerals. This plant has a wide geographical range and its leaves can be utilized without any negative impact on its growth and yield. An analysis was conducted to determine the calcium content in the fallen leaves, revealing a significant quantity of calcium that holds potential for utilization. The catalyst was characterized by different analytic techniques such as XRD, SEM-EDS, FT-IR, and BET analyses. Several parameters impacted on the transesterification process were exploited by conventional transesterification (batch). The result revealed that the optimum reaction was reached at a methanol to oil ratio of 50% w/w, catalyst loading of 3%, temperature of 65℃ and reaction time of 1.5 h with a yield of 93.21%, and the activation energy of the transesterification reaction was found to be 38.906 KJ mol-1. The reaction was verified to be irreversible pseudo-first order based on a linear Arrhenius plot and a high R2 value. The catalyst shows good stability and catalytic activity when it is reused and the yield was found to be 80.293% in the 5th cycle.